H1-Antihistamines Reduce the Risk of Hepatocellular Carcinoma in Patients With Hepatitis B Virus, Hepatitis C Virus, or Dual Hepatitis B Virus-Hepatitis C Virus Infection. Issue 11 (10th April 2022) - Shen, Yu-Chuan; Hsu, Hui-Ching; Lin, Tzu-Min; Chang, Yu-Sheng; Hu, Li-Fang; Chen, Lung-Fang; Lin, Sheng-Hong; Kuo, Pei-I.; Chen, Wei-Sheng; Lin, Yi-Chun; Chen, Jin-Hua; Liang, Yu-Chih; et al.
Abstract : PURPOSE: H1-antihistamines (AHs) may exert protective effects against cancer. This study investigated the association of AH use with the risk of hepatocellular carcinoma (HCC) in patients with hepatitis B virus (HBV), hepatitis C virus (HCV), or dual HBV-HCV virus infection. MATERIALS AND METHODS: Patients with HBV, HCV, or dual HBV-HCV infection were enrolled from Taiwan's National Health Insurance Research Database and examined for the period from January 1, 2006, to December 31, 2015. We used the Kaplan-Meier method and Cox proportional hazards regression to evaluate the association between AH use and HCC risk. RESULTS: We included patients with HBV infection (n = 521, 071), HCV (n = 169, 159), and dual HBV-HCV (n = 39, 016). Patients with HBV, HCV, or dual virus infection who used AHs exhibited significantly lower risk of HCC relative to patients who did not use AH, with their adjusted hazard ratio being 0.489 (95% CI, 0.455 to 0.524), 0.484 (95% CI, 0.450 to 0.522), and 0.469 (95% CI, 0.416 to 0.529), respectively. Furthermore, there was a dose-response relationship between AH use and the risk of HCC in the HBV cohort. The adjusted hazard ratios were 0.597 (95% CI, 0.530 to 0.674), 0.528 (0.465 to 0.600), 0.470 (0.416 to 0.531), and 0.407 (0.362 to 0.457) for AH use of 28-42, 43-63, 64-119, and ≥ 120 cumulative defined daily doses, respectively, relative to no AH use. Additionally, there was also a dose-response relationship between AH use and the risk of HCC in the HCV and dual HBV-HCV cohorts. CONCLUSION: AH use may reduce the risk for HCC among patients with HBV, HCV, or dual infection in a dose-dependent manner. Further mechanistic research is needed. Abstract :